SPORT AND MENTAL HEALTH LEVEL AMONG UNIVERSITY STUDENTS - Mouloud Kenioua; Abd Elkader Boumasjed (Physical Education of Students, 2016)
Purpose: study of mental health level of university student, athletes and non-athletes. Material: The tested group consisted of 160 male and female undergraduates from Ouargla University, Algeria; 80 students-athletes from Institute of Physical Education and Sports and 80 students-non-athletes from Department of Psychology, English and Mathematics. In the study we used health mental scale, adapted by Diab (2006) to Arab version scale, formed from five dimensions (Competence and self-confidence, Capacity for social interaction, Emotional maturity, Freedom from neurotic symptoms, self rating and aspects of natural deficiencies). Results: the findings indicated that university students have high level of mental health. And the mean of the responses of students-athletes group by mental health scale reached (M = 32.40), with standard deviation (STD =5.83), while the mean of the responses of students-non athletes group by mental health scale has reached (M=27.47), with standard deviation (STD=7.88). T-value, required to know significance of differences between means of students-athletes and students-non athletes has reached (T=4.51), (DF=185, p -0.01). So there are significant statistical differences between student athletes and non-athletes in their responses by mental health scale in favor of the student athletes. Conclusion:sports are beneficial in respect to mental health among university students and emphasizing the importance of the mental health of university students through its integration in the various recreational and competitive activities. Future qualitative research, covering multi-variables’ tests on mental health and others psychological characteristics could be performed in sports area.